Immersive History: Measuring the Impact of Virtual Reality (VR) on Empathy and Historical Retention - Lucas Lima; Omar Khan; Thabo Mokoena (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. Virtual Reality (VR) has emerged as an innovative educational technology that enables immersive learning experiences, particularly in history education where contextual understanding and perspective-taking are essential. Traditional instructional approaches often face limitations in fostering emotional engagement and sustaining long-term knowledge retention. Purpose. This study aims to examine the impact of VR on student empathy and historical retention, as well as to explore the relationship between immersive experience and learning outcomes in history education. Method. A quasi-experimental mixed-methods design was employed involving 104 students assigned to experimental (VR-based learning) and control (traditional instruction) groups. Data were collected through pretest–posttest assessments to measure retention, empathy questionnaires to assess affective responses, and qualitative reflections to capture students’ experiential insights. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis. Results. The findings indicate that VR significantly enhances both student empathy and historical retention compared to conventional instructional methods. A strong relationship is observed between immersive experience, emotional engagement, and improved memory outcomes. Empathy is identified as a mediating factor that strengthens the connection between immersion and knowledge retention. Conclusion. VR offers an effective pedagogical approach for integrating cognitive and affective dimensions of learning in history education. The results highlight the potential of immersive technologies to create meaningful and engaging learning experiences that support deeper understanding and long-term retention. Educators are encouraged to incorporate VR strategically to maximize both emotional engagement and academic achievement.